Does Emotional Intelligence Affect Social Adjustment Ability among Primary School Students? - Suyatno Suyatno; Khairil Nur Hidayat (Institute of Advanced Engineering and Science, 2018)
The aim of this research was to find out the impact of emotional intelligence to the social adjustment ability of the primary students in Muhammadiyah Karangwaru Yogyakarta Elementary School. The population involved in this research is all of the 5th grade students of Muhammadiyah Karangwaru Yogyakarta, who are 80 students. The sampling technique used here was Sampling Jenuh which then resulted 54 students as the samples of the research. The writer used questionnaire in collecting the data of the research. The approach used in the research was expost facto quantitative. Meanwhile in analyzing the data, the writer used simple regression test and test requirement. The result of the reserach shows that there is a positive and significant impact of emotional intelligence towards the social adjustment ability of the students. The acceptance hypothesis is showed through regression anlysis of Fcal which is 21.495 with significancy is 0.000. It can be defined that the ability of the students’ social adjustment can be improved through the improvement of their emotional intelligence. Based on the research result, this research suggests that it would be better if the learning process in the school gives more focus on the emotional intelligence formation which can affect to the development of social adjustment ability of the students. It is because the social adjustment ability constitutes a predictor of someone’s successful life in the future.